The Role of the Prospectus in the Application of the Disclosure Principle to the Franchise Cooperation Agreement - Liumenti, Liumenti; Urbaniasi, Urbaniasi (CV. Rayyan Dwi Bharata, 2023)
In today's business world, franchising is also known, which are generally carried out by companies and individuals who carry out business activities in the services, food and beverage sectors, such as fast food restaurants and cafes. Franchising in Indonesia is currently regulated in Government Regulation Number 42 of 2007 Concerning Franchising, this Government Regulation is stipulated to establish a balance between the parties in a franchise contract through various procedures that must be fulfilled by the franchisor and franchisee in a franchise business, mandatory procedures fulfilled by the parties in the franchise contract according to Government Regulation Number 42 of 2007 namely the Franchise Offer Prospectus. However, both the Franchisor and the Franchisee as parties to the franchise contract in practice in the business world in Indonesia until now very rarely understand the importance of the Franchise Offer Prospectus and are aware of the existence of the Franchise Offer Prospectus itself, this is due to a problem law, that is, the rule of law in the field of franchising is blurred. Thus this journal will discuss the Franchise Offer Prospectus Arrangements in the Franchise Agreement. The legal method used is the normative legal method, using primary data obtained from legal principles, comparisons of laws written in laws and regulations, as well as applicable norms and secondary data obtained by conducting library research. The results obtained in this study are that the arrangement of the franchise offer prospectus in the franchise agreement refers to article 7 of Government Regulation Number 42 of 2007 concerning franchising which is still general in nature and still needs to be corrected, so that the delivery of the Franchise Offer Prospectus by the Franchisor to the Prospective Franchisee is intended to the franchisee can carry out a business feasibility study on the franchise business that he will undertake.